The Structure of Withdrawals from ATMs Depending on Their Location Type - Gurgul, Henryk; Suder, Marcin (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
One of the main goals of ATMs’ management is a thorough analysis of the structure of withdrawals for individual ATM and groups of ATMs installed in similar places. This type of research constitutes a necessary background for decision making about the installation or de‑installation of ATMs in each location type. The most important factors from the point of view of the profitability of the ATM is the number of withdrawals and the value of a single withdrawal. A number of withdrawals from ATM determine the revenue of ATM owners due to interchange fees and advertisements displayed in ATMs at the time of withdrawal. A large number of withdrawals generate large revenues. The value of a single withdrawal has an impact on costs. The larger withdrawals generate larger costs including preparation and delivery of cash for an ATM and “freezing” of funds in the ATM. The main goal of this research was to identify locations of the ATMs generating largest revenues i.e. locations with a large number of withdrawals and small value of single withdrawal. In addition, we tested hypotheses concerning differences in a number of withdrawals and values of single withdrawals from ATMs installed in different types of locations. In this paper, we used a time series of numbers and values of withdrawals from ATMs supplied by one of the largest ATMs networks in Poland. The data set concerns ATM’s located in Małopolskie and Podkarpackie provinces in Poland. In the research concerning the structure of withdrawals, we have used basic descriptive statistics and selected statistical tests. The study concluded with the selection of locations where with high probability installation of ATM would generate profits. The results of the analysis may be of interest to owners of networks with respect of the choice of location type.